2013
DOI: 10.1007/s11252-013-0324-1
|View full text |Cite
|
Sign up to set email alerts
|

Movement and habitat use of the snapping turtle in an urban landscape

Abstract: In order to effectively manage urban habitats, it is important to incorporate the spatial ecology and habitat use of the species utilizing them. Our previous studies have shown that the distribution of upland habitats surrounding a highly urbanized wetland habitat, the Central Canal (Indianapolis, IN, USA) influences the distribution of map turtles (Graptemys geographica) and red-eared sliders (Trachemys scripta) during both the active season and hibernation. In this study we detail the movements and habitat u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Most of the studies about habitat use of freshwater turtles are focused on species from the Northern Hemisphere (Hartwig and Kiviat 2007;Haramura et al 2011;Millar and Blouin-Demers 2011;Forero-Medina et al 2012;Refsnider and Linck 2012;Wieten et al 2012;Hill and Vodopich 2013;Markle and Chow-Fraser 2014;Brown 2016;Pittfield and Burger 2017;Dupuis-Desormeaux et al 2018). But, only a few researchers have focused on how urbanization impacts the habitat of turtles (Ryan et al 2008;De Lathouder et al 2009;Refsnider and Linck 2012;Hill and Vodopich 2013;Ryan et al 2014;Brown 2016;Elston et al 2016;Ferronato et al 2016;Pittfield and Burger 2017). Ryan et al (2008) reported that human activities influence freshwater turtle habitat selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies about habitat use of freshwater turtles are focused on species from the Northern Hemisphere (Hartwig and Kiviat 2007;Haramura et al 2011;Millar and Blouin-Demers 2011;Forero-Medina et al 2012;Refsnider and Linck 2012;Wieten et al 2012;Hill and Vodopich 2013;Markle and Chow-Fraser 2014;Brown 2016;Pittfield and Burger 2017;Dupuis-Desormeaux et al 2018). But, only a few researchers have focused on how urbanization impacts the habitat of turtles (Ryan et al 2008;De Lathouder et al 2009;Refsnider and Linck 2012;Hill and Vodopich 2013;Ryan et al 2014;Brown 2016;Elston et al 2016;Ferronato et al 2016;Pittfield and Burger 2017). Ryan et al (2008) reported that human activities influence freshwater turtle habitat selection.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the spatial ecology and habitat requirements is essential to understand how urbanization impacts on the species, in order to effectively manage urban habitats (Ryan et al 2014). However, for most turtles this is poorly known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some species are able to remain, reproduce, and prosper in these urban areas (e.g. amphibians, reptiles, birds, mammals) (Ryan et al 2008(Ryan et al , 2014Rees et al 2009; Guzy et al 2013;Pereira et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies about basking of freshwater turtles relate to emydid species from the Northern Hemisphere (Lindeman, 1999;Moore and Seigel, 2006;Peterman and Ryan, 2009;Selman and Qualls, 2011;Millar, Graham and Blouin-Demers, 2012;Umphrey et al, 2012;Lambert et al, 2013;Ryan et al, 2014;Nyhof and Trulio, 2015;Vignoli et al, 2015). Despite this geographical bias, some general conclusions may be drawn: (1) the turtle's habitat requires the presence of basking surfaces on which turtles can easily climb to warm themselves (Umphrey et al, 2012); (2) the type of substrate and substrate preference vary among species (Ryan et al, 2008;Peterman and Ryan, 2009) and in relation to turtle age; and (3) in some species, large turtles spend more time basking than do small turtles (Lefevre and Brooks, 1995;Selman and Qualls, 2011).…”
Section: Introductionmentioning
confidence: 99%